Comparative review on information and communication technology issues in education sector of developed and developing countries: a case study about Pakistan - Aasma Akram; Mohsin Nazir; Tayyaba Batool; Muhammad Imran Zulfiqar; Maria Nazir; Habiba Azhar; Sadia Murawwat (Institute of Advanced Engineering and Science, 2021)
The use of information and communication technology is very beneficial in the education sector because it can enhance the quality of education. However, the implementation of ICT in the education sector of developed and developing countries is a challenging task. This paper explains the comparative study of ICT issues in the education sector of developed and developing countries. In particular, we compare issues between Pakistan and high-tech countries. Our study reveals the fact that the education sector is facing numerous ICT problems that are based on culture, finance, management, infrastructure, lack of training, lack of equipment, teacher’s refusal, and ethical issues. At the end of this paper, various issues faced by the implementation of ICT in the education sector of Pakistan have been categorized into various types, namely, infrastructure, lack of IT professionals, lack of high-speed internet and equipment. Our research is based on five key research questions related to ICT issues. We used a mixed approach where the results of this study can be used as a set of guidelines to help make the learning environment technology-oriented, fast, planned, and productive. Future directions are also given at the end of this paper.